AN APPRAISAL OF PRINCIPAL’S EFFECTIVE MANAGEMENT OF SCHOOL RESOURCES AS CORRELATE TO TEACHER’S JOB ACHIEVEMENT IN PUBLIC SECONDARY SCHOOLS IN EBONYI STATE - Ezenwagu, Stephen (UNIZIK Journal of Educational Management and Policy, 2023)
This study assess the Principal’s Effective Management of School Resources as Correlate to Teacher’s Job Achievement in Public Secondary Schools in Ebonyi State. In order to accomplish this objective, one specific purposes of the study and corresponding research question and hypothesis were guided the study. A comprehensive related literature was reviewed not only to serve as a guide to the research but also to give insight into what has already been done by other researchers in the related areas of the study. Correlational design was adopted for the study. The population of the study comprised of five thousand two hundred and ninety-eight (5,939) teachers in the public secondary schools in Ebonyi State. The sample of the study comprised five hundred and twenty (520) teachers. The instrument used for data collection was teachers’ assessment scale on principal’s effective management of economic resources and teachers job achievement. The instrument was validated by three experts, two experts from the Department of Educational Foundations and one expert from Measurement and Evaluation option of Science Education Department both in Ebonyi State University Abakaliki. The reliability co-efficient of the instrument was 0.86 and 0.78 respectively. Research questions and the hypotheses were tested using linear regression. Findings revealed that there is positive relationship between principals effective management economic resources and teachers’ job achievement in secondary schools in Ebonyi State; Based on the findings, the study recommended that various arms of the government especially those in charge of secondary education in the state should try to provide schools with the necessary resources needed by the schools principals for operation and management in the school.